Adjunct Training for Neurosurgeons from Low- and Middle-income Countries: A Scoping Review and Survey - Paul, Brian W.; Elahi, Cyrus; Rafka, Habib Emil; Sanker, Vivek; Poudel, Prabhat; Eberle, Adam T.; Dempsey, Robert J.; Vaughan, Kerry A.; Ellegala, Dilantha B.; Huguenard, Anna L.; Rahmani, Redi; Lawton, Michael T. (WFNS Journal, 2025)
Essential surgical care for individuals in low- and middle-income countries (LMICs) is lacking, particularly in neurosurgery. Despite global demand, neurosurgical trainees in LMICs face obstacles that include lack of funding, resources, educational opportunities, and clinical exposure. Supplemental education in the form of international fellowships, observerships, exchange programs, mission trips, and online courses can mitigate the gaps in neurosurgical training in LMICs. This scoping review explored existing global opportunities for supplemental neurosurgery training. Structured observership programs, international fellowships, international rotations, and online training modalities available to neurosurgical trainees in LMICs were compiled through a database and literature search. Additionally, international observers at Barrow Neurological Institute were surveyed to assess the effect of observership experiences on their clinical training. A comprehensive list of global opportunities was created, and seven categories of adjunct neurosurgical training for neurosurgeons from LMIC countries were identified: mission trips (n = 9), bidirectional exchange programs (n = 3), fellowships/in-person training (n = 26), observerships (n = 27), virtual training (n = 8), scholarships (n = 4), and international opportunities for US-based neurosurgery residents (n = 10). Survey results from the Barrow Neurological Institute observership program showed that 58 of 89 (65%) respondents found the experience “added a lot of value” to their clinical training, whereas 28 (31%) deemed the experience “indispensable.” Additionally, 67 of 94 (71%) reported increased comfort with complex cases. Participants cited increased clinical experience, mentorship, leadership, networking, and research as among the skills and opportunities gained. Supplemental neurosurgical training for LMICs offers substantial benefits by mitigating gaps in clinical training and improving skills and confidence.
Keywords: education; global neurosurgery; neurosurgery; observership; training